Karakteristik Morfometrik Hampala macrolepidota Kuhl & Van Hasselt, 1823 di Indonesia - Feby Dwi Restuningsih; Roza Elvyra; Haryono Haryono (Universitas Sam Ratulangi, 2023)
Hampala macrolepidota is a native fish in Indonesia that has potential as an ornamental fish and a consumption fish. The research aims were to determine the geographical classifying of fish and to analyze morphometric characteristics of H.macrolepidota morphology. The research was conducted at Fish Biosystematics Laboratory, Biosystematics and Evolution Research Center-BRIN Cibinong. Sample measured were 371 wet-preserved specimens of H. macrolepidota from various water lotic and lentic habitats in Indonesia using standard morphometric and truss morphometric methods. The collected data was analyzed using significance test with Wilk’s Lambda. Research result showed there is a tendency standard morphometrics is more accurate than truss morphometrics for classified H.macrolepidota according to their distribution area in Indonesia. This shows that H. macrolepidota on the islands of Sumatera, Jawa, and Kalimantan have a high similarity is due to the fact that the three islands are part of the Sunda Shelf.